Systematic Literature Review: Peran Akuntansi Forensik dan Fenomena Politik : Systematic Literature Review: The Role of Forensic Accounting and Political Phenomena - WILIANA, RAHAYU; Rachmadani, Febby; Wardani, Reski; Sastrawan, Randi (Universitas Bojonegoro, 2024)
The aim of this article is to explain the important role of forensic accounting in efforts to combat political corruption in order to obtain more comprehensive data and explanations. This research uses a Systematic Literature Review approach. The entire research process includes planning, implementation and reporting stages. The results of this research show that forensic accounting has proven to be very effective in detecting and disclosing corruption cases in budget management in an agency. The contribution to this research is that forensic accounting also has the potential to increase anti-fraud literacy among political parties through the implementation of a whistleblowing system. One of the main benefits of this system is its ability to carry out early detection of irregularities, whether in the form of fraud or non-fraud, committed by one or several employees in an organization.